2010
DOI: 10.1002/pola.24052
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected alternating radical copolymerization of chlorotrifluoroethylene with 3‐isopropenyl‐α,α′‐dimethylbenzyl isocyanate

Abstract: The radical solution copolymerization of hexafluoropropylene, chlorotrifluoroethylene (CTFE), vinylidene fluoride, and tert-butyl-a-trifluoromethylacrylate with different monomers bearing isocyanato groups such as allyl isocyanate, 3-isopropenyl-a,a 0 -dimethylbenzyl isocyanate (m-TMI), and 2isocyanatoethyl methacrylate, initiated by 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane were studied. Several of these radical copolymerizations were not successful in contrast to that of CTFE with m-TMI, although m-TMI mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 69 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…However, perfluoropolymers often suffer from poor solubility in common organic solvents and have difficult processing characteristics. As a result, an increasing amount of research in recent years have been focusing on the copolymerization of fluoroolefins and non-fluoro monomers to prepare semi-fluorinated polymers [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. Iodine transfer terpolymerization (ITP) was developed in the late 1970s by Tatemoto et al [26] and believed to be a suitable controlled radical polymerization (CRP) method for the polymerization of some fluoroolefins, especially for vinylidene fluoride (VDF) [27,28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, perfluoropolymers often suffer from poor solubility in common organic solvents and have difficult processing characteristics. As a result, an increasing amount of research in recent years have been focusing on the copolymerization of fluoroolefins and non-fluoro monomers to prepare semi-fluorinated polymers [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. Iodine transfer terpolymerization (ITP) was developed in the late 1970s by Tatemoto et al [26] and believed to be a suitable controlled radical polymerization (CRP) method for the polymerization of some fluoroolefins, especially for vinylidene fluoride (VDF) [27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the CRP methods have also been used in the (co)polymerization of fluoroolefins, such as VDF, chlorotrifluoroethylene (CTFE), 3,3,3-trifluoropropene (TFP), and hexafluoropropylene (HFP). Ameduri et al reported the synthesis of poly(VDF-co-TFP)- b -oligo(vinyl acetate) via the RAFT/MADIX process with fluorinated xanthate as a mediated agent [14]. Later on, another similar copolymerization process of perfluoro(methyl vinyl ether) and VDF was presented by Girard et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…As we know, living/controlled radical polymerization is a powerful tool for the synthesis of well-defined polymers with predetermined molar mass, low dispersity, and various architectures [67,68,69,70]. Some successful works focusing on the living/controlled radical (co)polymerization for fluoroolefins, such as vinylidene fluoride (VDF), tetrafluoroethylene (TFE), 3,3,3-trifluoropropene (TFP), hexafluoropropylene (HFP), and chlorotrifluoroethylene (CTFE), have been done in recent years [71,72,73,74,75,76,77,78,79,80,81]. RAFT/MADIX polymerization initiated by γ-rays seems to be very suitable for fluoroolefins.…”
Section: Introductionmentioning
confidence: 99%
“…13 Another possible method of reducing S mis-insertions is to utilize α-methyl styrene (AMS) as the comonomer in place of S. AMS has a very low ceiling temperature (61°C), therefore polymerization at or above this temperature results in a rate of depolymerization that is greater than the rate of homopolymerization. [17][18][19][20][21][22][23] TMI has also been shown to be capable of being homopolymerized and copolymerized cationically. 8 Although AMS-MalA copolymerization will provide control over the final copolymer substructure, well defined polymer molecular weight and polymer dispersity at present are not possible to obtain as controlled radical polymerization techniques, such as ATRP and RAFT, are ineffective for these monomers.…”
Section: Introductionmentioning
confidence: 99%
“…8 Although AMS-MalA copolymerization will provide control over the final copolymer substructure, well defined polymer molecular weight and polymer dispersity at present are not possible to obtain as controlled radical polymerization techniques, such as ATRP and RAFT, are ineffective for these monomers. 22,23,[25][26][27]30 In the present article, we exploit the free radical copolymerization behavior of functionalized TMI monomers with MalA to synthesize alternating copolymers that bear a desired moiety on every AMS repeat unit. [9][10][11][12][13][14][15] Furthermore, CCTP has been utilized to copolymerize mixtures of S/AMS and MalA, providing control over which monomer is present as the copolymer end group.…”
Section: Introductionmentioning
confidence: 99%